1996
DOI: 10.1002/bjs.1800831019
|View full text |Cite
|
Sign up to set email alerts
|

A 4-year prospective audit of the cause of death after infrarenal aortic aneurysm surgery

Abstract: This study was a 4-year prospective audit of abdominal aortic aneurysm surgery including 222 aneurysm repairs: 106 elective, 76 urgent and 40 emergency. Twenty-five patients died: four who underwent elective surgery, seven urgent and 14 emergency. The two major causes of death, multiple organ failure and colonic ischaemia, were responsible for 11 of the 25 deaths. The three deaths from myocardial infarction all occurred in patients with a leaking aneurysm. Blood loss was significantly higher in patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…We confirmed previous investigators' findings that rAAA is an independent CI risk factor. 6,7,9 Female gender has been associated with rAAA at presentation and increased mortality risk, but gender has not previously been associated with an increased risk of CI. 32 Explanations for the increased risk of CI associated with female gender are not forthcoming from the current literature, but the increased risk may reflect differences in case difficulty, aneurysm anatomy, thrombus characteristics, or the degree of visceral collateral circulation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We confirmed previous investigators' findings that rAAA is an independent CI risk factor. 6,7,9 Female gender has been associated with rAAA at presentation and increased mortality risk, but gender has not previously been associated with an increased risk of CI. 32 Explanations for the increased risk of CI associated with female gender are not forthcoming from the current literature, but the increased risk may reflect differences in case difficulty, aneurysm anatomy, thrombus characteristics, or the degree of visceral collateral circulation.…”
Section: Discussionmentioning
confidence: 97%
“…5 Although the incidence of CI after major vascular surgery is relatively low (approximately 1%-6%), development in this setting is associated with high mortality rates up to 90%, depending on both patient factors (advanced age, underlying medical illness, ruptured AAA [rAAA]) and the physiologic insult (fluid shifts, prolonged operative and cross-clamp time, sacrifice of inferior mesenteric or hypogastric artery collaterals, blood loss, sepsis) associated with repair. [5][6][7][8][9] Relatively small reports of CI after EVAR have documented an incidence of approximately 1% to 6%. [10][11][12][13][14][15] Unlike open repair in which the onset is thought to occur from a global physiologic insult, the pathogenesis of CI after EVAR is thought to be due to dislodged debris from the aneurysm sac or from iliofemoral access.…”
mentioning
confidence: 98%
“…Open repair of AAA is a major operation that is usually associated with significant blood loss. Previous studies have shown that average intraoperative blood loss ranges from 750 mL to 1700 mL 1,2,10,11 . Blood loss commonly occurs during opening of the aneurysm sac and from back‐bleeding of the lumbar arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Open repair of abdominal aortic aneurysm (AAA) is a major operation that carries a mortality of 1.6−7.5% and morbidity of 13−23% 1,2 . High intraoperative blood loss was found to be associated with multiorgan failure and bowel ischaemia 2 , and increased rate of mortality and morbidity 3,4 . These undesirable effects may be attributed to hypotension or systemic inflammatory response after excessive blood and fluid transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Trata-se de uma infreqüente porém grave complicação da cirurgia de aorta abdominal, sendo o cólon sigmóide o segmento mais afetado (2,3,4,5). Quando é considerado apenas o quadro clínico, a incidência de isquemia colônica após a correção de dilatações aneurismáticas da aorta abdominal é de aproximadamente 1% a 2% (1,2,3,6,7,8,9).…”
Section: Introductionunclassified